Is patient experience of care associated with treatment choices for women with early-stage breast cancer?. Issue 28 (1st October 2022) - Halpern, Michael T.; McNeel, Timothy S.; Kozono, David E.; Mollica, Michelle
Abstract : 289 Background: For women diagnosed with early stage breast cancer, lumpectomy followed by radiation therapy is a guideline-recommended treatment. However, lumpectomy followed by hormonal therapy is also an approved treatment regimen for certain women. It is unclear what patient-driven factors are related to the decision to receive radiation therapy. This study examined the relationship between patient-reported experience of care, an important dimension of health care quality, and receipt of radiation therapy following lumpectomy among women with breast cancer. Methods: We used the SEER-CAHPS data resource (NCI Surveillance Epidemiology and End Results [SEER] data linked to Medicare Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey responses) to examine experiences of care among women diagnosed with local or regional stage breast cancer in 2000-2017 who received lumpectomy, were enrolled in fee-for-service Medicare, completed a CAHPS survey within 18 months of diagnosis, and survived for this study period. Experience of care was assessed by patient-provided numeric scores for overall care, health plan, physicians, customer service, doctor communication, care coordination, and other aspects of care. Multivariable logistic regression models assessed associations of receipt of radiation therapy with care experience and patient sociodemographic and clinical characteristics. Results: The study population included 825 women; 651 (79%) received radiation therapy. Approx. 84% were diagnosed with localized (vs. regional) breast cancer. Women with higher experience scores for their personal doctor or for care coordination were significantly more likely to have received any radiation therapy. In contrast, among women enrolled in Medicare Part D plans, those who reported higher scores for their prescription drug plan were significantly less likely to have received radiation therapy. Conclusions: Patient experience of care was significantly associated with receipt of radiation therapy following lumpectomy among women with breast cancer. While these results do not show causality, future quality improvement initiatives may want to explore the role of patient experience of care in facilitating patient decision making and improving quality of care.